Work engagement and learning goal orientation: what's the connection? - Tan, Fee Yean; Johari, Johanim; Yahya, Khulida Kirana (2017)
The purpose of this study is to examine the influence of work engagement on academicians' learning goal orientation. This is a cross-sectional study, where data were collected through questionnaire from a sample of academicians (n = 265) attached to Malaysian public universities. The regression results indicated that work engagement is the key factor that influences academicians' learning goal orientation. From the findings obtained, the proposed relationship is substantially validated. The findings do not only benefit academicians in particular, from the aspect of their engagement and learning goal orientation, but also Malaysian public universities, in general, from the aspect of the enrichment of university's performance. This study includes a detailed discussion of the research findings as well as the theoretical and practical ramifications of this study.